Deteksi Keberadaan Bakteriofag pada Tanaman Padi yang Terinfeksi Xanthomonas oryzae pv. oryzae di Sentra Produksi Padi Daerah Istimewa Yogyakarta - Dea Musytari Intan Irpawa; Triwidodo Arwiyanto; Sri Sulandari; Nanang Kurniawan (Politeknik Negeri Lampung, 2026)
Bacterial Leaf Blight (BLB), caused by Xanthomonas oryzae pv. oryzae (Xoo), is one of the most significant diseases affecting rice crops in Indonesia. Conventional control strategies still face various limitations, particularly regarding their efficacy and environmental impacts. This study aimed to detect the presence of bacteriophages as potential biological control agents against Xoo in the rice production centers of the Special Region of Yogyakarta. A total of 20 samples, including soil, water, and symptomatic rice leaves, were collected from infected rice fields. Plaque assays were performed to detect bacteriophage presence, followed by host range evaluations against 20 Xoo isolates. The results showed that 18 out of 20 samples produced plaques, indicating the presence of bacteriophages capable of lysing Xoo. Soil samples demonstrated a broader host range compared to water and leaf samples. These findings highlight the immense potential of bacteriophages as specific and eco-friendly biological control agents against BLB in the Yogyakarta region.